1987
DOI: 10.1007/bf00191379
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur retention at intensively studied sites in the U.S. and Canada

Abstract: We compiled and summarized current literature on S input/output budgets for intensively studied sites and soil plots in the U.S. and Canada and found S retention to be related to both soil order and extent of the last glaciation (Wisconsinan). Zero net retention is associated with Spodosols and was found only at sites north of the limit of Wisconsinan glaciation. Sites south of the limit of glaciation appear to be retaining from 20 to 90% of incoming S. These findings support the hypothesis that there exist re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(27 citation statements)
references
References 27 publications
1
25
0
1
Order By: Relevance
“…The somewhat greater nitrate fluxes at West Branch could potentially be a result of nitrate loading from septage or other anthropogenic sources, and/or from net mineralization due to land disturbance on the mountain. Sulfate export is in approximate balance with estimated S inputs at Ranch Brook, as is typical for northeastern USA watersheds (Rochelle et al, 1987;Likens and Bormann, 1995). The greater export of sulfate at West Branch is most likely caused by the weathering of sulfides in the Hazens Notch Formation which underlies most of that basin.…”
Section: Discussionmentioning
confidence: 97%
“…The somewhat greater nitrate fluxes at West Branch could potentially be a result of nitrate loading from septage or other anthropogenic sources, and/or from net mineralization due to land disturbance on the mountain. Sulfate export is in approximate balance with estimated S inputs at Ranch Brook, as is typical for northeastern USA watersheds (Rochelle et al, 1987;Likens and Bormann, 1995). The greater export of sulfate at West Branch is most likely caused by the weathering of sulfides in the Hazens Notch Formation which underlies most of that basin.…”
Section: Discussionmentioning
confidence: 97%
“…10 Input-output fluxes (mol ha −1 ) and % retention of SO 2À 4 for the six selected storm events 10 Fitzhugh et al (2001) Otter Creek Drainage, West Virginia, USA 100-150 b 11 Nodvin et al (1995) Nolan Divide watershed, North Carolina/Tennessee, USA 20-60 a converted from mg/L; b derived from figure groundwater sources. Rochelle et al (1987) and Galloway et al (1983) attributed the differences in sulfate retention among northern and southern regions of the North American continent to the extent of the last glaciation (Wisconsin) and the consequent impact on weathering and soil formation. Rochelle et al (1987) found that sites north of the limit of the glaciation had zero net retention while sites south of the line were retaining 20 to 90% of the incoming S. Sulfate concentrations in watershed compartments at the Point Peter Brook watershed ( Table 2) clearly suggest that groundwaters were the largest source of SO 2À 4 to the streams.…”
Section: Flow-weighted So 2àmentioning
confidence: 99%
“…Rochelle et al (1987) and Galloway et al (1983) attributed the differences in sulfate retention among northern and southern regions of the North American continent to the extent of the last glaciation (Wisconsin) and the consequent impact on weathering and soil formation. Rochelle et al (1987) found that sites north of the limit of the glaciation had zero net retention while sites south of the line were retaining 20 to 90% of the incoming S. Sulfate concentrations in watershed compartments at the Point Peter Brook watershed ( Table 2) clearly suggest that groundwaters were the largest source of SO 2À 4 to the streams. We attribute the high concentrations of SO 2À 4 in groundwater to the contributions of the weathering of S-containing minerals.…”
Section: Flow-weighted So 2àmentioning
confidence: 99%
“…Adsorption is an important mechanism of sulphate retention in soils rich in iron and aluminium hydrous oxides (Johnson et al, 1982); however, adsorbed sulphate generally comprises less than 30% of the total sulphur pool in soils located north of the most recent continental glaciation (Rochelle et al, 1987;Mitchell et al, 1992;Houle and Carignan, 1995). Precipitation of aluminium hydroxy sulphate minerals may also be an important means of sulphate retention in extremely acidic soils subject to high levels of sulphur input (Khanna et al, 1987).…”
Section: Introductionmentioning
confidence: 98%